Marijuana Is Associated With a Hormonal Imbalance Among Several Habits Related to Male Infertility: A Retrospective Study - Teixeira, Thiago A.; Iori, Ivan; Andrade, Gustavo; Saldiva, Paulo H. N.; Drevet, Joël R.; Costa, Elaine M. F.; Hallak, Jorge (Frontiers in Reproductive Health, 2022)
Marijuana is one of the most consumed drugs worldwide. There is increasing evidence of an association between marijuana and male infertility. This study intends to assess the repercussion of marijuana smoking and other habits (sedentary lifestyle, alcohol and tobacco use) in the testicular function of infertile men seeking andrological evaluation. A retrospective study was performed using medical records data of men aged 18-59 years from 2009 to 2017. Complete semen analyses, sperm functional tests, SHBG, and hormonal levels, testosterone-to-estradiol ratio (T/E2), and testis volume were evaluated. Exclusion criteria included cryptorchidism, infertility caused by genetic or infectious diseases, and cancer. A multiple linear regression analysis was performed to investigate which habit could predict certain parameters using the software SPSS 23.0 (P<0.05). In a sample of 153 men, semen parameters, testosterone levels, and testis volume were not significantly influenced. Marijuana use had the broader hormonal changes since it influences estradiol (P=0.000; B=-11.616), prolactin (P=0.000; B=3.211), SHBG levels (P=0.017; B=7.489) and T/E2 (P=0.004; B=14.030). Sedentary lifestyle (P=0.028; B=1.279) and tobacco smoking (P=0.031; B=-2.401) influenced the prolactin levels. Marijuana is associated with hormonal imbalance in this infertile cohort, by lowering estradiol levels and inhibiting aromatase function.